2005
DOI: 10.1089/jir.2005.25.63
|View full text |Cite
|
Sign up to set email alerts
|

The HPV-16 E7 Oncogene Sensitizes Malignant Cells to IFN-α-Induced Apoptosis

Abstract: Interferons (IFNs) exert antitumor effects in several human malignancies, but their mechanism of action is unclear. There is a great variability in sensitivity to IFN treatment depending on both tumor type and the individual patient. The reason for this variable sensitivity is not known. The fact that several IFN-induced anticellular effects are exerted through modulation of proto-oncogenes and tumor suppressor genes may indicate that the malignant genotype may be decisive in the cell's sensitivity to IFN. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…On the other hand, the altered cellular networks of molecular pathways that sustain growth of cancer cells can paradoxically offer novel tools for cancer therapy. For example, it has been shown that HPV-E7 oncogene can sensitize malignant cells to IFN--induced apoptosis, indicating that oncogenic events may also increase cell sensitivity to IFNs [228]. Together with others, we have shown how S-phase cell accumulation appears to be a common response of tumor cells to type I IFNs.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, the altered cellular networks of molecular pathways that sustain growth of cancer cells can paradoxically offer novel tools for cancer therapy. For example, it has been shown that HPV-E7 oncogene can sensitize malignant cells to IFN--induced apoptosis, indicating that oncogenic events may also increase cell sensitivity to IFNs [228]. Together with others, we have shown how S-phase cell accumulation appears to be a common response of tumor cells to type I IFNs.…”
Section: Discussionsupporting
confidence: 77%
“…This could also lead to a decreased amount of papilloma cells, but with maintained levels of virus. IFN-a has been shown to act proapoptotically in neoplastic cells and we have recently found that expression of the HPV16 E7 oncogene may sensitize tumour cells to IFN-induced apoptosis (Thyrell et al, 2005). Whether induction of apoptosis explains the clinical effects of IFN-a in respiratory papillomatosis, however, remains to be investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Spontaneous loss of the HPV early protein E2, involved in plasmid replication and viral DNA transcription, has been associated with both increased expression of anti‐viral genes inducible by type 1 IFN and release of the viral oncoproteins E6 / E7 63. Recent studies have also found that transfection of malignant cells with the E7 oncogene can sensitize them to IFN‐alpha‐induced apoptosis 64, and a lack of immune response in cervical cancer has been correlated with high expression levels of HPV16‐ E7 65. This suggests that active, persistent oncogenic HPV infection may alter the cellular sensitivity to IFN in tumour tissue, and might also have implications for IFN‐based treatments of HPV‐related diseases including HNSCC.…”
Section: Discussionmentioning
confidence: 99%